Effect of moisture, bale type, and a preservative on alfalfa hay quality and feeding value - Laytimi, A.; Arledge, J.; Grimes, C.; Bolsen, K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In the first of two alfalfa hay experiments, lambs fed small bale hays averaged 16% better gains and feed conversions than those fed large bale hays; Fresh Cut®-treated hay gave 9% better performance than untreated hays; and medium-moisture hays produced 12% faster and more efficient gains than low-moisture hays. In the second experiment, hay baled above 30% moisture had excessive heating, more discoloration and mold growth, higher storage losses, and lower dry matter and protein digestibilities compared with 15% moisture hay.
Keywords: Beef; Moisture; Bale type; Preservative; Hay quality; Value